Sabal antillensis (Arecaceae): a new palmetto species from the Leeward Antilles - Griffith, M. Patrick; Freitas, John De; Barros, Michelle; Noblick, Larry R. (Phytotaxa, 2017)
A new species of palmetto, Sabal antillensis, native to Curaçao and Bonaire, is described and illustrated. The new species is characterized by a pachycaulous habit, a compact crown of leaves, large seeds, and frequent fiber bundles in leaflet transection. Details on history, morphology, distribution, habitat, and conservation status are provided.